From slum to tourist attraction: mural in India Street Kuching, Sarawak / Mursyidah Zainal Abidin ... [et al.] - Zainal Abidin, Mursyidah; Jimel, Clement; Mohd Rathi, Mohd Razif; Wasli, Zaidi; Haini, Mohd Faizol (Universiti Teknologi MARA, 2020)
The City of the Cat or better known as Kuching is a city that is rich with cultural diversity and tourist attractions such as cultural events, monuments with the essence of local culture, historical buildings and public arts. There are abandoned areas in the heart of the City that pose a potential threat to the tourism industry. The researchers, with the help of Kuching North City Hall, have identified the spot that is located at the corner of Indian Street to be the perfect location for the artistic makeover. This is because the area is abandoned, filthy and known as the 'back alley' where the drunks hang out and dirty the place with rubbish and urine. This paper focuses on the transformation of the area from 'slum' to tourist attraction using art. It is a collaboration project between Kuching North City Hall and the Faculty of Art & Design, UiTM Sarawak, to enhance the artistic ambience of the city. Since Tourism is one of the key sources of the state's income, this project hopes to yield more tourist attractions to Sarawak. Furthermore, the project aims to revitalize the 'forgotten' areas in the city through art to add to the repertoire of tourist attractions in the city.